Basics of Parametric thinking and workflow: Exploring the possibilities of parametric design (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There was been a rapid technology advancement in all fields after that 20th century thusarchitecture needs to use advance design forming technology to improve and detail out the aspects ofdesign efficiently therefore Parametric Design is a set of parameters provided by the site converted intoan algorithm which a computer software then create a responsive design that can be tweaked to thedesigner‟s requirement and Fluidity is a state of being unsettled or a form that is smooth and creates asense of motion. Patrik Schumacher, who at the time was a partner at Zaha Hadid Architects, coined theterm „parametricism‟. Parametric design has particularly rebelled against long-established guidelines. Dueto the idea that “form follows function”, modern architecture is more of a science than an art form, whichcreates a monotonous skyline with straight lines and box shapes. Parametricism, on the other hand,focuses on free-form architectural concepts. Sweeping lines, curves, and irregular shapes give eachbuilding character. Such designs might appear futuristic or otherworldly. In the study, I aimed tounderstand and apply parametric as a design tool, as well as learn about parametric design thinkingComputer aided Geometric design, and methods for applying parametric in different fields of design.